Exosomes Derived from Astragaloside IV-pretreated Endothelial Progenitor Cells (AS-IV-Exos) Alleviated Endothelial Oxidative Stress and Dysfunction via the miR-210/ Nox2/ROS Pathway - Xiong, Wu; Zhang, Xi; Zou, Xiao-Ling; Peng, Sai; Lei, Hua-Juan; Liu, Xiang-Nan; Zhao, Lan; Huang, Zi-Xin (Current Molecular Medicine, 2025)
Background Chronic hyperglycemia in diabetes induces oxidative stress, leading to damage to the vascular system. In this study, we aimed to evaluate the effects and mechanisms of AS-IV-Exos in alleviating endothelial oxidative stress and dysfunction caused by high glucose (HG). Methods Histopathological changes were observed using HE staining, and CD31 expression was assessed through immunohistochemistry (IHC). Cell proliferation was evaluated through CCK8 and EDU assays. The levels of ROS, SOD, and GSH-Px in the skin tissues of each group were measured using ELISA. Cell adhesion, migration, and tube formation abilities were assessed using adhesion, Transwell, and tube formation experiments. ROS levels in HUVEC cells were measured using flow cytometry. The levels of miR-210 and Nox2 were determined through quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The expression of Nox2, SOD, GSH-Px, CD63, and CD81 was confirmed using WB. Results The level of miR-210 was reduced in diabetes-induced skin damage, while the levels of Nox2 and ROS increased. Treatment with AS-IV increased the level of miR-210 in EPC-Exos. Compared to Exos, AS-IV-Exos significantly reduced the proliferation rate, adhesion number, migration speed, and tube-forming ability of HG-damaged HUVEC cells. AS-IV-Exos also significantly decreased the levels of SOD and GSH-Px in HG-treated HUVEC cells and reduced the levels of Nox2 and GSH-Px. However, ROS levels and Nox2 could reverse this effect. Conclusion AS-IV-Exos effectively alleviated endothelial oxidative stress and dysfunction induced by HG through the miR-210/Nox2/ROS pathway.
Keywords: endothelial dysfunction